Effect of ivermectin (Baymec) on natural psoroptic and sarcoptic scab in sheep - Ozer, E; Saki, CE; Sevgili, M (Tubitak Scientific & Technological Research Council Turkey, 1998)
This study was carried out in sheep with natural psoroptic scab in Kamisli village of Kovancilar town in Elazig province and in sheep with natural sarcoptic scab in Kovancilar town between April and May in 1996. According to the intensity of Psoroptes ovis and Sarcoptes ovis, two groups, control and treatment, each of which contained 15 sheep were formed in the flock with psoroptic scab whereas the flock with sarcoptic scab were divided into control and treatment groups containing 10 sheep each. Within the trial period, animals in the treatment group and the other animals in both flock received subcutaneous injection of ivermectin (Baymec) (O.2 mg/kg body weight) twice at 10 days intervals. Control animals were subjected to the same treatment as above at the and of the experiment. Effect of ivermectin P.ovis was 60% on the 10th day of the first administration, 88.7% on the 10th day of the second administration and 100% on the 20th day. In terms of S.ovis, these values were found to be 70%, 90% and 100% respectively. it was also observed that clinical symptoms decreased gradually and disappeared at the end of the experiment.
Koyunlarda Do?al Psoroptic ve Sarcoptic Uyuza İvermectin (Baymec)'in Etkisi
Keywords: sheep; Psoroptes ovis; Sarcoptes ovis; ivermectin